Creating positive contexts of reception: The value of immigrant teachers in U.S. early childhood education programs - Adair, Jennifer Keys (Education Policy Analysis Archives, 2016)
Young children of immigrants are increasingly part of early childhood programs in the United States but teachers have mixed approaches and attitudes about the immigrant families that they work with. This article details an analysis of 50 preschool teachers in five US cities using data from the Children Crossing Borders video-cued ethnographic study. The analysis finds that preschool sites that valued the insight of immigrant teachers had more positive views of immigrant communities and stronger mechanisms to communicate with immigrant parents. The article ultimately argues that policies that support the presence and meaningful input of immigrant preschool teachers can help preschool sites be positive, rather than negative or indifferent, contexts of reception.